Post larval stages of Tanytydeus beyzavii sp. nov. (Acari: Paratydeidae) from Iran - Khanjani, Mohammad; Nadri, Ali Reza; Khanjani, Masoumeh; Seeman, Owen D. (Zootaxa, 2014)
A new species Tanytydeus beyzavii sp. nov. (Acari: Paratydeidae) is described and illustrated from soil under plants in Iran. Leg setation is presented for the genus, as is a key to species. The genus Hexatydeus syn. nov. is synonymised with Tanytydeus because the former represent nymphal stages of Tanytydeus.